2021
DOI: 10.1039/d1cc00306b
|View full text |Cite
|
Sign up to set email alerts
|

Benzylic C–H addition of aromatic amines to alkenes using a scandium catalyst

Abstract: An efficient and selective benzylic C(sp3)-H addition of o-CH3-substituted tertiary aromatic amine to alkene has been achieved using an anilido-oxazoline ligand supported scandium catalyst, which provides an atom-economic method for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…In particular, half-sandwich rare-earth complexes showed unique activities and selectivities in catalytic C–H additions to a variety of alkenes and alkynes . In our prior work, we showed that the cationic rare-earth-metal complexes supported by unsymmetric β-diketiminato-type ligands enabled the versatile C–H functionalization of anilines, such as para -C­(sp 2 )–H alkylation with alkenes, C­(sp 2 )–H/N–H annulation with allenes and dienes, α-C­(sp 3 )–H alkylation with alkenes, and benzylic C­(sp 3 )–H alkylation with alkenes . These reactions demonstrated promising results, owing to the strong nitrogen affinity of rare-earth-metal ions.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In particular, half-sandwich rare-earth complexes showed unique activities and selectivities in catalytic C–H additions to a variety of alkenes and alkynes . In our prior work, we showed that the cationic rare-earth-metal complexes supported by unsymmetric β-diketiminato-type ligands enabled the versatile C–H functionalization of anilines, such as para -C­(sp 2 )–H alkylation with alkenes, C­(sp 2 )–H/N–H annulation with allenes and dienes, α-C­(sp 3 )–H alkylation with alkenes, and benzylic C­(sp 3 )–H alkylation with alkenes . These reactions demonstrated promising results, owing to the strong nitrogen affinity of rare-earth-metal ions.…”
supporting
confidence: 89%
“…12 In our prior work, we showed that the cationic rare-earth-metal complexes supported by unsymmetric β-diketiminato-type ligands enabled the versatile C−H functionalization of anilines, such as para-C(sp 2 )−H alkylation with alkenes, 13 C(sp 2 )−H/N−H annulation with allenes and dienes, 14 α-C(sp 3 )−H alkylation with alkenes, 15 and benzylic C(sp 3 )−H alkylation with alkenes. 16 These reactions demonstrated promising results, owing to the strong nitrogen affinity of rare-earth-metal ions. Further study herein disclosed that a scandium complex based on a simple β-diketiminato ligand could also be applied for the benzylic C(sp 3 )−H addition of tertiary ortho-methyl anilines to a variety of internal alkynes with high chemo-and stereoselectivity (Scheme 1c).…”
mentioning
confidence: 99%
“…Recently, the Xu group reported Sc-catalyzed ortho -benzylic C–H alkylation of tertiary anilines 170a using various alkenes 170b , which rendered moderate to good yields (Scheme 170). 269 The easily available anilido-oxazoline ligand bound Sc-complex enabled the reaction with high atom economy, a good substrate scope, high functional group tolerance and substrate-dependent regioselectivity. The reaction proceeded via the generation of cationic monoalkyl Sc-species 170h with the help of [PhNHMe 2 ][B(C 6 F 5 ) 4 ].…”
Section: Alkylation Via C–h Bond Activationmentioning
confidence: 99%
“…Recognizing these aspects, recently Xu and co-workers demonstrated the selective benzylic sp 3 C–H addition of ortho -methyl N , N -dimethylaniline scaffolds with allylarenes and unactivated aliphatic alkenes in the presence of a non-metallocene bulky β-diketiminato-type anilido-oxazoline ligand-supported Sc-dialkyl complex as catalyst 12 -Sc in combination with catalytic [PhNHMe 2 ][B(C 6 F 5 ) 4 ] as an activator (Scheme 16A). 97 The Y analogue of 12 -Sc was found to be ineffective for the transformation, which is most likely because the ligand framework could not stabilize the cationic active species of the Y centre. Perhaps this report represents the first example of achieving the sp 3 C–H alkylation of the benzylic methyl group of anilines with alkenes under Sc catalysis.…”
Section: Group 3 Metal Catalysismentioning
confidence: 99%